Fragmentation Dynamics of Fluorene Explored Using Ultrafast XUV-Vis Pump-Probe Spectroscopy - Garg, D.; Lee, J. W. L.; Tikhonov, D. S.; Chopra, P.; Steber, A. L.; Lemmens, A. K.; Erk, B.; Allum, F.; Boll, R.; Cheng, X.; Düsterer, S.; Gruet, S.; et al. (Frontiers in Physics, 2022)
We report on the use of extreme ultraviolet (XUV, 30.3 nm) photons from the Free-electron LASer in Hamburg (FLASH) and visible (Vis, 405 nm) photons from an optical laser to investigate the relaxation and fragmentation dynamics of fluorene ions. The ultrashort laser pulses allow to resolve molecular processes occurring on the femtosecond timescales. Fluorene is a prototypical small polycyclic aromatic hydrocarbon (PAH). Through their infrared emission signature, PAHs have been shown to be ubiquitous in the universe, and they are assumed to play an important role in the chemistry of the interstellar medium. Our experiments track the ionization and dissociative ionization products of fluorene through time-of-flight mass spectrometry and velocity-map imaging. Multiple formation channels for each of the fragment ions are disentangled and relaxation lifetimes of the excited fluorene mono-cation and di-cation on the femtosecond timescale are reported.